2010
DOI: 10.1016/j.annemergmed.2010.01.014
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Evaluation of Emergency Department Bedside Ultrasonography for the Detection of Acute Cholecystitis

Abstract: Study objective: We assess the diagnostic accuracy of emergency physician-performed bedside ultrasonography and radiology ultrasonography for the detection of cholecystitis, as determined by surgical pathology. Methods:We conducted a prospective, observational study on a convenience sample of emergency department (ED) patients presenting with suspected cholecystitis from May 2006 to February 2008. Bedside gallbladder ultrasonography was performed by emergency medicine residents and attending physicians at an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
103
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(114 citation statements)
references
References 32 publications
3
103
1
1
Order By: Relevance
“…There are also studies proving the accuracy and advantages of US performed in emergency as compared to hepato- [22,23] or computer tomography [24] .Summers and Colab. studied a better accuracy of US performed in the emergency setting than that of the same method performed by radiologists for the identificationof surgical conditions such as acute cholecystitis [25] .The originality of the study resides in the correlation of the clinical and ultrasonographic aspects with intra-operatory findings, as well as in the analysis of sonographicrole in the diagnosis of different forms of cholecystitis.The incidence of acute cholecystitis was higher in female patients,andmost of the patient who complain of acute calculuscholecystitis created at age between (41-50) years old, The results of the present study confirm the variations in lithiasis incidence, as stated in the epidemiological literature [26,27] . We also found an increased incidence of the disease in patients from an urban areas, revealed that most of Khartoum population complain a lot from (ACC) ,represent71% ,comparewith Kassala and Omdurman.…”
Section: Discussionsupporting
confidence: 79%
“…There are also studies proving the accuracy and advantages of US performed in emergency as compared to hepato- [22,23] or computer tomography [24] .Summers and Colab. studied a better accuracy of US performed in the emergency setting than that of the same method performed by radiologists for the identificationof surgical conditions such as acute cholecystitis [25] .The originality of the study resides in the correlation of the clinical and ultrasonographic aspects with intra-operatory findings, as well as in the analysis of sonographicrole in the diagnosis of different forms of cholecystitis.The incidence of acute cholecystitis was higher in female patients,andmost of the patient who complain of acute calculuscholecystitis created at age between (41-50) years old, The results of the present study confirm the variations in lithiasis incidence, as stated in the epidemiological literature [26,27] . We also found an increased incidence of the disease in patients from an urban areas, revealed that most of Khartoum population complain a lot from (ACC) ,represent71% ,comparewith Kassala and Omdurman.…”
Section: Discussionsupporting
confidence: 79%
“…11 EPs have become more adept at fracture diagnosis through independent review of US and radiographic imaging, and many researchers have examined the ability of EPs to obtain US imaging and diagnose fracture. 12,13 Additionally, bedside US has excellent diagnostic test characteristics when performed by EPs compared to radiologists in the diagnostic evaluation for soft tissue infections, 14 cholecystitis, 15 pneumothorax, 16 or ruling out ectopic pregnancy.…”
Section: Resultsmentioning
confidence: 99%
“…Ultrasound can be helpful in identifying the source of infection [8][9][10][11]; it can help define and monitor the hemodynamic status of the patient via evaluation of inferior vena cava, heart and lung water [12][13][14]; it can guide invasive procedures in both diagnosis (sampling) and treatment (drainage) [15].…”
Section: Discussionmentioning
confidence: 99%